Exploring the first-time transition to parenthood in mainland China: a qualitative study on the experiences of fathers and mothers using the transition shock model - Lang, Xi; Zeng, Tieying; Ni, Sha; Jiang, Lingjun; Qian, Pan; Wu, Meiliyang (Frontiers in Psychology, 2024)
Background: The transition to parenthood, which is influenced a lot by local parenting culture, is a dramatic stress for both men and women.Chinese social and cultural contexts form specific parental culture, shaping the unique experience of transition to parenthood. However, the understanding of the transition to parenthood in mainland China is limited. Additionally, few qualitative studies explored the transition to parenthood from both dyadic perspectives.Aim: To explore the first-time transition to parenthood experience among mothers and fathers in mainland China during pregnancy, and compare the similarities and differences between their experiences in this transition period.Methods: A descriptive qualitative study was conducted with 36 parents, including 18 primiparous women and their husbands. Data were analyzed by directed content analysis guided by the Transition Shock Model. The interview texts were first analyzed at individual levels and subsequently at the couple level to identify dyadic themes.Results: Five themes and thirteen sub-themes emerged from the data analysis, including role integration, health risk, dilemma of preparation, protective isolation, and multi-dimensional expectation. Unexpectedly, the experiences and perspectives of mothers and fathers regarding the transition to parenthood were found to be similar, with the exception of the sub-theme extra-care requirement.Conclusions: The findings shed light on the complex emotional journey and expectations of parents, as well as the challenges they face in terms of physical well-being, limited coping resources, and restricted social connections. Notably, fathers in China often shared the stress of the whole process during the transition period alongside mothers but often lacked accessible avenues for seeking and receiving support.These findings underscore the importance of actively involving fathers as a key support population in perinatal care, as well as the need for comprehensive support systems and tailored interventions to enhance the well-being and adaptation of parents.